Human capital, service innovation advantage, and business performance: The moderating roles of dynamic and competitive environments. Issue 9 (5th September 2016) - Prajogo, Daniel I.; Oke, Adegoke
Abstract : Purpose: The purpose of this paper is to examine the effect of human capital (HC) on service innovation advantage (SIA) and business performance (BP) in service sector firms, and how external environmental factors influence these relationships. Design/methodology/approach: This study utilized a cross-sectional mail survey of a random sample of Australian service firms with the unit of analysis being at the firm level. In total, 228 usable responses were received. Findings: The overall findings of this study show that HC is positively related to the creation of value or SIA which in turn results in rent generation for firms. The results further show that the effect of SIA on BP is influenced by environmental dynamism and competitiveness with dynamic environments enhancing the effect while competitive environments weakening it. Research limitations/implications: The findings demonstrate the complementarity between the resource based theory and contingency theory as they clearly shows that the value of innovation as a firm's capability is enhanced or weakened within a business environment that is more dynamic or competitive. Practical implications: The findings demonstrate the importance of HC, and, thus, encourage managers to seek ways to harness and leverage HC for improving innovation and BP. In addition, the study also helps managers to understand the contingency effect of business environment on the effectiveness of innovation, hence, helping them in deliberating firms' strategy in different business environments. Originality/value: To the best of the authors' knowledge, this is the first study which examines the effectiveness of HC as organizational resource for building SIA as a source of organizational competitive advantage.